Bridging the Gap: Identifying Needs and Aspirations of Indigenous Students to Facilitate their Entry into University - Hossain, Delwar; Gorman, Don; Williams-Mozely, John; Garvey, Darlene (The Australian Journal of Indigenous Education, 2008)
Abstract The negative trend of enrolment of Indigenous students into tertiary study indicates gaps between their current achievement and knowledge levels and university requirements for admission. This study was designed to determine the perceived needs, attitudes and knowledge of Indigenous secondary school students when considering admission to university; investigate remedial strategies in order to make university a more attractive choice for Indigenous students; and ascertain the types of assistance and support the Indigenous students would like to receive in order to meet the enrolment requirements as well as completion of study at university. Focus groups were conducted with 50 Indigenous students in Years 10 to 12 within the Toowoomba District and surveys conducted with 30 first year Indigenous undergraduate and Indigenous Higher Education Pathways Program (IHEPP) students at the University of Southern Queensland. The findings of the research illustrated that the school students were not aware of the IHEPP and university programs. Scholarships and bursaries need to be developed and publicised. Tutorial assistance and learning support (e.g., assignment preparation, multicultural activities, childcare facilities, group accommodation) needs to be promoted. Furthermore, there is a need for the university to establish and maintain relationships with local Indigenous communities and understand the “cultural dimension” impacting on Indigenous students and their families.